0
$\begingroup$

I was calculating equations,

p2 := 1 e + r M1^2
p1 := 1 + r M2^2
p2/p1/.M2-> Sqrt[((r - 1)/(2 r))]
Simplify@%/.e -> 0

where e : to remove by approximation that M1 is close to infinite(term of M1 is very large then other term, since neglect other term)

This results is

(2 M1^2 r)/(1 + r)

I want to make result as

(2 r)/(1 + r) *  M1^2

And why these result cannot be simple form

T2 := 1 ϵ + (r - 1)/2 M1^2
T1 := 1 + (r - 1)/2 M2^2
ρ2 := M1 Sqrt[T1]
ρ1 := M2 Sqrt[T2]
$Assumtions = r > 0;
$Assumtions = M1 > 1;
ρ2/ρ1 // Refine // FullSimplify
% /. M2 -> Sqrt[(r - 1)/(2 r)]
% /. ϵ -> 0 // Simplify

enter image description here

$\endgroup$
0
$\begingroup$
p2 := 1 e + r M1^2
p1 := 1 + r M2^2
p2/p1 /. M2 -> Sqrt[((r - 1)/(2 r))]
expr = Simplify@% /. e -> 0

enter image description here

If you want a non-standard (to Mathematica) form you have to force it

Inactive[Times][Coefficient[expr, M1^2], M1^2]

enter image description here

You misspelled $Assumptions

T2 := 1 ϵ + (r - 1)/2 M1^2
T1 := 1 + (r - 1)/2 M2^2
ρ2 := M1 Sqrt[T1]
ρ1 := M2 Sqrt[T2]
$Assumptions = {r > 0, M1 > 1};
ρ2/ρ1 // FullSimplify (* Refine is unnecessary *)
% /. M2 -> Sqrt[(r - 1)/(2 r)]
% /. ϵ -> 0 // Simplify

enter image description here

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.